Self-Care, Sense Of Coherence And Depression In Patients Hospitalized For Decompensated Heart Failure - Viviane Martinelli Pelegrino Ferreira; Luma Nascimento Silva; Rejane Kiyomi Furuya; André Schmidt; Lídia Aparecida Rossi; Rosana Aparecida Spadoti Dantas (SciELO, 2015)
OBJECTIVE To analyze the self-care behaviors according to gender, the symptoms of depression and sense of coherence and compare the measurements of depression and sense of coherence according to gender. METHOD A correlational, cross-sectional study that investigated 132 patients with decompensated heart failure (HF). Data were collected through interviews and consultation to medical records, and analyzed using the chi-square and the Student's t tests with significance level of 0.05. Participants were 75 men and 57 women, aged 63.2 years on average (SD = 13.8). RESULTS No differences in self-care behavior by gender were found, except for rest after physical activity (p = 0.017). Patients who practiced physical activity showed fewer symptoms of depression (p<0.001). There were no differences in sense of coherence according to self-care behavior and gender. Women had more symptoms of depression than men (p = 0.002). CONCLUSION Special attention should be given to women with HF considering self-care and depressive symptoms.